2011
DOI: 10.1534/genetics.111.129445
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Mapping of Complex Traits with Phenotype-Based Selection and Introgression

Abstract: Finding the genes underlying complex traits is difficult. We show that new sequencing technology combined with traditional genetic techniques can efficiently identify genetic regions underlying a complex and quantitative behavioral trait. As a proof of concept we used phenotype-based introgression to backcross loci that control innate food preference in Drosophila simulans into the genomic background of D. sechellia, which expresses the opposite preference. We successfully mapped D. simulans introgression regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
(30 reference statements)
0
31
0
Order By: Relevance
“…19 and 21 and Dataset S6) and attraction QTLs (ref. 18 and C. D. Jones, personal communication) present outside of putative low recombination regions. We found that just 3 of 13 attraction QTLs overlapped a window with PBE greater than 0.125 (P = 0.200).…”
Section: Genome-wide Scan Of Targets Of Natural Selection In Mayottementioning
confidence: 97%
See 2 more Smart Citations
“…19 and 21 and Dataset S6) and attraction QTLs (ref. 18 and C. D. Jones, personal communication) present outside of putative low recombination regions. We found that just 3 of 13 attraction QTLs overlapped a window with PBE greater than 0.125 (P = 0.200).…”
Section: Genome-wide Scan Of Targets Of Natural Selection In Mayottementioning
confidence: 97%
“…QTLs were drawn from mapping studies of noni attraction (ref. 18 and C. D. Jones, personal communication) and tolerance to noni or octanoic acid (19,21). QTL positions were obtained with respect to the D. yakuba genome.…”
Section: Hybridization and Mate Choice Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, several proof-of-principle studies, each applying different approaches to successfully map a chemically induced mutation using WGS, have been documented in the literature (Sarin et al 2008Blumenstiel et al 2009;Zhang et al 2009;Earley and Jones 2011;Fairfield et al 2011;Andrews et al 2012;Bull et al 2013). In general, a subset of SNVs is first removed based on assay-specific criteria upon which some form of mapping is performed to reduce the number of candidate mutations.…”
mentioning
confidence: 99%
“…While this may be true for variation associated with a small number of large-effect alleles, a much larger number of lines may be necessary to attain sufficient statistical power when phenotypic variation is caused by many smaller-effect alleles (Long and Langley 1999). For this reason, we propose that population-based resequencing of artificially selected populations provides a powerful compliment to GWAS in D. melanogaster (Nuzhdin et al 2007;Burke et al 2010;Earley and Jones 2011;Turner et al 2011;Zhou et al 2011). This approach is not limited by the creation and maintenance of large sets of inbred lines and could therefore be leveraged in other species of Drosophila, other insects, annual plants, and any other system where large populations can be manipulated over multiple generations (Johansson et al 2010;Parts et al 2011).…”
mentioning
confidence: 99%